Work–life balance/imbalance: the dominance of the middle class and the neglect of the working class - Warren, Tracey (Wiley, 2015)
The paper was stimulated by the question of class in work-life debates. The common conclusion from work-life studies is that work-life imbalance is largely a middle class problem. It is argued here that this assertion is a direct outcome of a particular and narrow interpretation of work-life imbalance in which time is seen to be the major cause of difficulty. Labour market time, and too much of it, dominates the conceptualisation of work-life and its measurement too. This heavy focus on a certain type of work-life imbalance: chronometric overstretched temporal imbalance, has rendered largely invisible from dominant work-life debates the types of imbalance that are more likely to impact the working class. Looking at working class employees in the UK, this paper asserts that ‘too few’ hours working also has work-life ramifications. It thus argues for the necessity of analysing economic – and not just temporal - roots of work-life imbalance. The paper concludes that if we are to continue to pursue work-life analysis, the conceptualisation of work-life needs to more full incorporate economic-based imbalance if it is to better represent class inequalities.